The genetic architecture of genome‐wide recombination rate variation in allopolyploid wheat revealed by nested association mapping. (19th July 2018) - Jordan, Katherine W.; Wang, Shichen; He, Fei; Chao, Shiaoman; Lun, Yanni; Paux, Etienne; Sourdille, Pierre; Sherman, Jamie; Akhunova, Alina; Blake, Nancy K.; Pumphrey, Michael O.; Glover, Karl; et al.
Summary: Recombination affects the fate of alleles in populations by imposing constraints on the reshuffling of genetic information. Understanding the genetic basis of these constraints is critical for manipulating the recombination process to improve the resolution of genetic mapping, and reducing the negative effects of linkage drag and deleterious genetic load in breeding. Using sequence‐based genotyping of a wheat nested association mapping (NAM) population of 2, 100 recombinant inbred lines created by crossing 29 diverse lines, we mapped QTL affecting the distribution and frequency of 102 000 crossovers (CO). Genome‐wide recombination rate variation was mostly defined by rare alleles with small effects together explaining up to 48.6% of variation. Most QTL were additive and showed predominantly trans ‐acting effects. The QTL affecting the proximal COs also acted additively without increasing the frequency of distal COs. We showed that the regions with decreased recombination carry more single nucleotide polymorphisms (SNPs) with possible deleterious effects than the regions with a high recombination rate. Therefore, our study offers insights into the genetic basis of recombination rate variation in wheat and its effect on the distribution of deleterious SNPs across the genome. The identified trans ‐acting additive QTL can be utilized to manipulate CO frequency and distribution in the large polyploid wheat genome opening the possibility to improve the efficiency of gene pyramiding and reducing the deleterious genetic load in the low‐recombining pericentromeric regions of chromosomes. Significance Statement: This study offers insights into the genetic basis of recombination rate variation in allopolyploid wheat and its effect on the distribution of deleterious SNPs across the genome. The identified trans ‐acting additive recombination rate QTL can be utilized to manipulate crossover frequency and distribution in the large polyploid wheat genome opening the possibility to improve the efficiency of gene pyramiding and reducing the deleterious genetic load in the low recombining pericentromeric regions of chromosomes.